Fashion film e OBC (Online Brand Community): forme di dialogo fra immaginario e algoritmo - Simonetta Buffo (Ocula)
The aim of this paper is to outline the most recurring forms of interaction between Fashion Films and Online Brand Community, starting from an internal research project at IULM University. After having conducted a semiotic analysis of the imageries presented in some Brandsâ Fashion Films, we investigated subsequently how digital communities (OBC) interact with them on YouTube. The results obtained have led to some reflections regarding how digital videos work and what users appreciate the most, and suggesting the purpose that Fashion Films actually achieve.